The Linking of Brand Personality, Trust, Attitude and Purchase Intention of Halal Cosmetic in Indonesia; A Conceptual Paper - Rubiyanti, Nurafni; Mohaidin, Zurina (International Journal of Engineering and Technology, 2018)
The growth of Indonesian cosmetic industry opens the market opportunity for halal cosmetic. Most of cosmetic industry is dominated by international brands otherwise local brands take the opportunity of the niche market by offering halal cosmetic products. To strive in the competition among companies, they must have a good strategy in sell the product to consumers. A broad exploration of previous research was conducted, and found that it is important for company to understand the consumer purchase intention. It was found that brand personality, trust, and attitude were considered become significant factors influencing the purchase intention. It is hoped that this conceptual paper will trigger better understanding on what factors influence purchase intentions of purchasing Halal cosmetic products.Â Â
Keywords: Brand Personality; Trust; Attitude; Purchase Intention.